Differential gene expression reflects morphological characteristics and physiological processes in rice immunity against blast pathogen Magnaporthe oryzae - Azizi, Parisa; Yusop, Mohd Rafii; Mahmood, Maziah; Abdullah, Siti Nor Akmar; Musa, Mohamed Hanafi; Nejat, Naghmeh; Abdul Latif, Muhammad; Sahebi, Mahbod (Public Library of Science, 2015)
The rice blast fungus Magnaporthe oryzae is a serious pathogen that jeopardises the world's most important food-security crop. Ten common Malaysian rice varieties were examined for their morphological, physiological and genomic responses to this rice blast pathogen. qPCR quantification was used to assess the growth of the pathogen population in resistant and susceptible rice varieties. The chlorophyll content and photosynthesis were also measured to further understand the disruptive effects that M. oryzae has on infected plants of these varieties. Real-time PCR was used to explore the differential expression of eight blast resistance genes among the ten local varieties. Blast disease has destructive effects on the growth of rice, and the findings of our study provide evidence that the Pikh, Pi9, Pi21, and Osw45 genes are involved in defence responses in the leaves of Malaysian rice at 31 h after inoculation with M. oryzae pathotype P7.2. Both the chlorophyll content and photosynthesis were reduced, but the levels of Pikh gene expression remained constant in susceptible varieties, with a developed pathogen population and mild or severe symptoms. The Pi9, Pi21, and Osw45 genes, however, were simultaneously upregulated in infected rice plants. Therefore, the presence of the Pikh, Pi9, Pi21, and Osw45 genes in the germplasm is useful for improving the resistance of rice varieties.